Chaos-Enhanced Cuckoo Search for Economic Dispatch with Valve Point Effects - M. W. Mustafa; Abdirahman M. Abdilahi; M. Mustapha (Universitas Ahmad Dahlan, 2016)
Economic dispatch determines the optimal generation outputs to minimize the toal fuel cost while satisfying the load demand and operational constraints. Modern optimization techniques fail to solve the problem in a robust manner and finding robust global optimization techniques is necessary for efficient system operation. In this study, the potentiality of introducing chaos into the standard Cuckoo Search (CS) in order to further enhance its global search ability is investigated. Deterministic chaotic maps are random-based techniques that can provide a balanced exploration and exploitation searches for the algorithm. Four different variants are generated by carefully choosing four different locations (within the standard CS) with potential adoption of a candidate chaotic map.Then detailed studies are carried out on benchmark power system problems with four different locations to find out the most efficient one. The best of all test cases generated is chosen and compared with algorithms presented in the literature. The results show that the proposed method with the proposed chaotic map outperforms standard CS. Additionally, the chaos-enhanced CS has a very good performance in comparison with QPSO and NSS.